Pengaruh Jus Buah Mentimun, Tomat, dan Jambu Biji Terhadap Penurunan Tekanan Darah Tinggi Pada Pasien Penderita Hipertensi - Fatmawati Jasus (Jurnal Ilmu Gizi Indonesia (JIGZI), 2020)
AbstractHigh blood disease is a disease classified as the silent killer. One solution is by giving cucumber juice, tomato juice, and guava juice. The purpose of this study was to determine the effect of the three kinds of juice on the decrease in blood pressure in patients with hypertension.  High blood disease is a disease classified as the silent killer. One solution is by giving cucumber juice, tomato juice, and guava juice. The purpose of this study was to determine the effect of the three kinds of juice on the decrease in blood pressure in patients with hypertension.  The results obtained mean systolic pressure before given 147 cucumber juice and diastolic pressure 90.2. While the mean systolic pressure after given cucumber juice was 138.8 and the diastolic pressure was 82.5. The results obtained mean systolic pressure before given 140,3 tomato juice and 86.8 diastolic pressure. While the mean systolic pressure after being given tomato juice was 132.8 and the diastolic pressure was 79.5. The results obtained mean systolic pressure before given guava juice 140.8 and diastolic pressure 88,7. While the mean systolic pressure after guava juice was given 127.5 and the diastolic pressure was 81.0. Provision of cucumber juice, tomato juice and guava juice is quite influential in lowering blood pressure in patients with hypertension, so it is expected that health workers, especially nurses are more active in providing counseling about the use of these three juices to decrease blood pressure in people with hypertension.Keywords : Hypertension, Cucumber Juice, Tomato Juice, Guava Juice